2010
DOI: 10.5114/aoms.2010.19308
|View full text |Cite
|
Sign up to set email alerts
|

Randomized study assessing the influence of supervised exercises on ankle joint mobility in patients with venous leg ulcerations

Abstract: IntroductionThe aim of the study was to assess the influence of a supervised programme of exercises on ankle joint mobility in patients with venous leg ulcerations.Material and methodsThe study was carried out between 2008 and 2009 at the Venous Ulcer Treatment Outpatient Clinic and Clinic of General and Vascular Surgery of the Dr Jan Biziel University Hospital no. 2 in Bydgoszcz. It was a randomized control study in which 32 patients with venous leg ulcerations were qualified. Patients with ulcerations were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0
15

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(51 citation statements)
references
References 17 publications
0
36
0
15
Order By: Relevance
“…Details of each of the included studies are summarised in Table . Settings were diverse, including outpatient clinics, university hospitals, and patient homes (Table ). Primary outcomes differed among the studies, although all studies reported wound characteristics (time to heal, proportion of ulcers healed, and ulcer recurrence).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Details of each of the included studies are summarised in Table . Settings were diverse, including outpatient clinics, university hospitals, and patient homes (Table ). Primary outcomes differed among the studies, although all studies reported wound characteristics (time to heal, proportion of ulcers healed, and ulcer recurrence).…”
Section: Resultsmentioning
confidence: 99%
“…Three studies described adequate methods of allocation sequence and concealment and were at low risk of selection bias (Figure ). The remainder ( n = 3) reported these methods unclearly and were at risk of selection bias. All studies were at risk of performance bias, with none of the studies reporting adequate participant blinding.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Chronic venous insufficiency and ulceration, as well as post-treatment cicatrix can be associated with ankle joint abnormalities -its reduced mobility affecting plantar and dorsal flexure of the foot and associated deficiency of muscle-articular pump, a mechanism that stimulates the venous return together with the vascular-valvular system regulating the value of hydrostatic pressure [19,20].…”
Section: Secondary Preventionmentioning
confidence: 99%